A Resequencing-Based Ultradense Genetic Map of Hericium erinaceus for Anchoring Genome Sequences and Identifying Genetic Loci Associated With Monokaryon Growth - Gong, Wenbing; Xie, Chunliang; Zhou, Yingjun; Zhu, Zuohua; Wang, Yahui; Peng, Yuande (Frontiers in Microbiology, 2020)
Hericium erinaceus has attracted tremendous interest due to its compelling health-promoting properties. However, breeding of elite cultivars of H. erinaceus is hindered by the lack of a genetic and molecular toolbox. Here, we performed re-sequencing analysis of 127 F1 single spore isolates and constructed the first high-resolution genetic map of H. erinaceus. Using recombination bins as markers, an ultra-dense genetic map consisting of 1,174 bins (including 37,082 single nucleotide polymorphisms) was generated. This newly developed genetic map covered 1,096.5 cM, with an average bin spacing of 0.95 cM. High collinearity between genetic map and H. erinaceus genome assembly was revealed by aligning scaffolds to this genetic map using bin markers as anchors. The application of this newly developed genetic map in quantitative trait locus (QTL) mapping was also elucidated, and four QTLs for monokaryon growth were recovered. One QTL, mgr1, which contributes 12.1% of growth variations, was located near the mating type A (MAT-A) loci. Overall, this newly constructed high-resolution genetic map (or bin map) could be used as reference in future genetic, genomic, and breeding studies on H. erinaceus.